Effect of scion defoliation and stock leaf retention on growth of grafted lime (cv. Bau lime-1) - Nahar, Ashrafun; Choudhury, Md Shahidul Haque; Rahim, Md Abdur (Asian Journal of Medical and Biological Research, 2018)
The present experiment was conducted at the Germplasm Centre (GPC) of the Fruit Tree Improvement Program (FTIP), Bangladesh Agricultural University, Mymensingh, during the period from June to October, 2013 to investigate the effects of scion defoliation and stock leaf retention on growth of grafted Lime (cv. BAU lime-1). The experiment consisted of two factors such as Factor A: four scion defoliation periods viz., defoliation before 9 days of grafting, defoliation before 6 days of grafting, defoliation before 3 days of grafting and defoliation on the day of grafting and Factor B: retention of leaf on rootstock below graft union viz., rootstock with leaf and rootstock without leaf. The study was laid out following Randomized Complete Block Design (RCBD) with three replications. The grafts were kept under observation in poly tunnel condition. Results revealed that highest graft height, (45.47 cm), number of leaves (15.72) and branches (2.92), length of the largest leaf(8.45cm), breadth of the largest leaf(3.77cm) were observed when scions were defoliated 6 days before grafting and lowest graft height (38.72 cm), number of leaves (12.12) and branches (2.25), length of the largest leaf(5.60cm), breadth of the largest leaf(3.37cm) were observed when scions were defoliated on the day of grafting. In respect of retention of leaves on rootstock, the highest graft height (43.83 cm), number of leaves (15.62) and branches (2.82), length of the largest leaf(7.47cm), breadth of the largest leaf(3.78cm) were found when grafting was done on rootstock with leaves and lowest graft height (39.78 cm), number of leaves (11.32) and branches (2.48), length of the largest leaf(6.57cm), breadth of the largest leaf(3.40cm) were found when grafting was done on rootstock without leaves. Therefore, the maximum growth in grafted lime seedlings can be achieved if scion defoliated 6 days prior to grafting operation and leaves are kept on root stock below graft union. Asian J. Med. Biol. Res. March 2018, 4(1): 44-48